Inovasi dalam Lembaga Pendidikan - Putri, Rizky Ananda; Khoriroh, Fitri; Zohriah, Anis; Firdaos, Rijal (Peneliti.net, 2025)
Educational innovation is an effort to overcome existing challenges in education. Innovation in the educational context can take the form of various things, be it products or systems. For example, a teacher can create learning media in the form of mock ups to improve the quality of learning. The educational innovation model at the Indonesian Ministry of Education and Culture still tends to use a